Community Based Resources: Mengembangkan Kapasitas Komunitas GKJ Jeruklegi Margi Rahayu Menuju Sejahtera - Agustini Respati; Purwani Retno Andalas; Xaveria Prasasyaningsih; Putriana Kristanti*; Pristanto Silalahi; Albertus Nugroho (Universitas Lancang Kuning, 2023)
GKJ Jeruk Legi is a religious-based community in Cilacap Regency. Founded in 2014, this church has a congregation of around 250 people. Single congregations come from very varied backgrounds, with the majority being women and having completed their bachelor's degrees. Seeing from eyes of workers can be seen as domestic workers, contractors, culinary, vegetable trading, minimal water depots, livestock, and agriculture. Even so, most people still have problems in terms of welfare. Through a project management approach, this activity proposes a triangulation of solutions, including optimizing the livestock and agricultural sectors, developing entrepreneurship through asset families, and the initiation and aspirations of cooperatives. Through project management and triangulation of solutions, it is hoped that these activities can be structured coherently to achieve welfare goals and increase the economy. The evaluation results showed that most of the community succeeded in obtaining knowledge related to the triangulation of solutions for goals.